NEW TRENDS IN TECHNOLOGY AND CHAT BOTS - Hamada, Samir; AlShibli, Mohammad; Hamada, Salwa (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
As a result of ChatGPT's (Conversational Generative Pre-training Transformer) popularity, the teacher is concerned that students might use it to do their homework and assignments. In this paper, we will discuss ChatGPT, the fields in which it is used, and how to make it useful in education.